DEVELOPING ENGLISH VOCABULARY LIST AT PELITA II PRIMARY SCHOOL BY USING RANGE - Mutiara, Rika (Jurnal Pengabdian Masyarakat AbdiMas, 2017)
AbstractThis community service project aims at introducing the use of Range in materials development to the English teachers at SD Pelita II. It, moreover, gave assistance to the teachers. Range is software which categorizes the vocabulary based on how frequent they are used in daily life. The teachers need to develop vocabulary lists from authentic materials and students’ texts. The lists would be used for developing learning materials. To know this, vocabulary measurement should be done. Measuring vocabulary can be done easier by using Range. Having the data provided by this program gave consideration for the teachers what vocabulary should be included. The teachers were given tutorial on how to use Range. In this phase, they practiced with the help of the tutor. Then, they worked independently to build their own vocabulary lists and made conclusions about the texts being analyzed based on the information provided by Range. Finally, the teachers decided which vocabulary needs to get more attention on learning materials because they are necessary to be acquired by the students. In addition, the teachers also chose which authentic texts are more appropriate by considering students’ level of fluency. To sum up, Range is helpful for developing materials especially vocabulary of the texts. Keywords: vocabulary, learning materials, Range AbstrakProgram pengabdian masyarakat ini bertujuan untuk memperkenalkan penggunaan program Range dalam pengembangan materi ajar kepada guru Bahasa Inggris di SD Pelita II. Program ini juga membimbing guru untuk dapat menggunakan Range. Range adalah perangkat lunak yang dapat mengategorikan kosakata berdasarkan seberapa sering kosakata tersebut digunakan dalam kehidupan sehari-hari. Untuk mengembangkan materi ajar, guru di SD Pelita II perlu mengembangkan daftar kosakata dari materi autentik dan teks buatan siswa. Untuk melakukan hal tersebut, pengukuran kosakata perlu dilakukan. Pengukuran kosakata dapat dilakukan dengan lebih mudah dengan menggunakan Range. Data yang dihasilkan dari program ini memberikan pertimbangan bagi guru mengenai kosakata yang perlu dimasukan ke dalam materi ajar. Guru mengikuti tutorial mengenai penggunaan Range. Dalam tahap ini, guru berlatih dengan bantuan tutor. Selanjutnya, mereka bekerja secara independen untuk menciptakan daftar kosakata dan membuat kesimpulan tentang kosakata dalam teks yang diteliti berdasarkan informasi yang diberikan oleh Range. Guru memutuskan kosakata mana yang perlu untuk menjadi fokus pembelajaran karena penting bagi siswa untuk menguasai kosakata tersebut. Selain itu, guru juga memilih teks autentik mana yang lebih tepat untuk digunakan dalam pengembangan materi ajar dengan mempertimbangkan kemahiran siswa berbahasa Inggris. Range berguna untuk mengembangkan materi ajar khususnya kosakata dalam teks. Kata kunci: kosakata, materi ajar, Range